Mineral Phosphate Solubilizing Bacteria Isolated from Various Plant Rhizosphere under Different Aluminum Content - Damarjaya, Dolly Iriani; Widada, Jaka; Senoo, Keishi; Nishiyama, Masaya; Otsuka, Shigeto (Indonesian Journal of Biotechnology, 2005)
The objectives of this study was to isolate and characterize the mineral phosphate solubilizing bacteriafrom rhizosphere and evaluate their potential as plant growth promoting bacteria in Al-toxic soils. The halozone formation method was used to isolate PSB using the media containing insoluble phosphates (Ca-P or Al-P)as a source of phosphate. Eight of acid and Al-tolerant PSB isolates that were able to solubilize Ca-P wereobtained from rhizosphere of clover, wheat, corn, and sunflower grown in Al-toxic soil. Identification of theisolates based on the 16S rRNA gene sequence analysis demonstrated that the isolates were strains of Burkholderia(5 strains), Pseudomonas (1 strain), Ralstonia (1 strain), and unidentified bacterium (1 strains). All PSB isolatesshowed the capability to dissolve Ca-P, and only 1 strain (Ralstonia strain) was able to dissolve Al-P in agar platemedium. The P-solubilization by these isolates was correlated with pH of medium. Inoculation of the bacterialstrains on clover on Al-toxic medium showed that all isolates increased the plant dry weight compared withuninoculated treatment. Our results showed that those PSB isolates have potential to be developed as a biofertilizerto increase the efficiency of P-inorganic fertilizer used in Al-toxic soils.